Preparing a mixture of wheat and urad dal for a ceremony - Mumbai Archive Project Team (Jio Institute, 2024)
On the day before the wedding, a special ceremony is conducted to prepare a mixture of wheat and urad dal (split black gram lentil). This mixture is ritually offered at the shrine of the grihadevata (household deity). Subsequently, the rice is distributed among the wedding guests who attend the ceremony to bless the bride and groom.